Inter-imperiality : Vying Empires, Gendered Labor, and the Literary Arts of Alliance - Doyle, Laura (Laura Anne) (Book collections on Project MUSE., 2020)
"In this work, Laura Doyle weaves together feminist-intersectional, decolonial, and dialectical thought to challenge narratives of world history at new depths while also reviving our sense of historical dynamism. Her analysis of the intertwining of literature with geopolitical economy makes visible an underlying struggle over the very terms of relationality. Meticulously informed by new historiography on empires and by critical theory, Doyle's study highlights the geopolitical fact of multiple vying empires in any one period and focuses on the uncertain, unequal, existential conditions created by this field of power over millennia"--